L’occitan et le développement socio-économique et culturel du territoire : l’exemple du PNR Aubrac - Caroline Calvet (Lengas)
While keeping linguistic and socio-cultural diversity could be one of the conditions for the development of vulnerable areas and one of the challenges facing future generations, this publication sets out to examine the place of Occitan in the enhancement, development and promotion of territory, and more specifically within the Aubrac Regional Natural Park (PNR Aubrac). Significant examples of the productivity and exploitation of this ethnosociolinguistic richness are presented based on a toponymic survey, a sociolinguistic survey and a corpus of interviews carried out in 2022 within the PNR Aubrac. So, while the heritage value of Occitan could be a way to enhance and develop the area, we need to look at the way in which the area's institutions, local protagonists and residents are taking advantage of this ethnosociolinguistic vitality: how are structured the actions and measures to promote Occitan, and what are their issues?